Exotic Universalism & The New Petite Bourgeoisie: An Analysis of Yoga Marketing on Instagram - Simonds, Colin H. (Bodhi: An Interdisciplinary Journal, 2022)
This paper works towards an understanding of how modern postural yoga is promoted in new media and the role of class therein. The paper analyzes the content of four yoga Instagram profiles to discern how the contemporary postural practice is marketed on social media. In doing so, it demonstrates how yoga practitioners and organizations position their practice as both exotic and universal. This twofold movement establishes their product (yoga classes and studios) as unique yet accessible in the marketplace of spirituality and fitness. While these two processes of exoticisation and universalisation seem contradictory, this paper argues that this dissonance is emblematic of the values of the new petite bourgeoisie, a socio-economic class which serves as the main source of cultural capital in contemporary neoliberal societies.